IMPLEMENTASI CLOUD COMPUTING DAN APLIKASI ONLYOFFICE DENGAN KEAMANAN INTRUSION DETECTION SYSTEM PADA RASPBERRY PI - Ngatono, Ngatono; Septian, Dika Gilang; Rahmat, Rahmat (Jurnal Ilmiah Sains dan Teknologi, 2021)
The development of increasingly advanced technology affects a system and efficiency in the world of entrepreneurship. Store owners have difficulties in creating, processing, storing data and lack of network security. Therefore, cloud computing is very much needed as a storage medium, in addition to the importance of cloud computing in Toko Titik, it also really needs data processing applications to make it easier to work and network security to avoid external attacks. To overcome this, the author will design a cloud computing with Nextcloud software, onlyoffice application as a data processor and network security with IDS (Intrusion Detection System) on the Raspberry Pi. From the results of research conducted, it has been proven that with cloud computing, storage media is more effective and efficient. Nextcloud can also be accessed on Android anytime and anywhere as long as there is internet, and also data processing using the Onlyoffice application installed on NextCloud. Of course this is very easy for entrepreneurs to store data and process data, coupled with network security so that data security is maintained